Scaling the Aspect Ratio of Nanoscale Closely Packed Silicon Vias by MacEtch: Kinetics of Carrier Generation and Mass Transport. (10th February 2017) - Kim, Jeong Dong; Mohseni, Parsian K.; Balasundaram, Karthik; Ranganathan, Srikanth; Pachamuthu, Jayavel; Coleman, James J.; Li, Xiuling
Abstract : Metal‐assisted chemical etching (MacEtch) has shown tremendous success as an anisotropic wet etching method to produce ultrahigh aspect ratio semiconductor nanowire arrays, where a metal mesh pattern serves as the catalyst. However, producing vertical via arrays using MacEtch, which requires a pattern of discrete metal disks as the catalyst, has often been challenging because of the detouring of individual catalyst disks off the vertical path while descending, especially at submicron scales. Here, the realization of ordered, vertical, and high aspect ratio silicon via arrays by MacEtch is reported, with diameters scaled from 900 all the way down to sub‐100 nm. Systematic variation of the diameter and pitch of the metal catalyst pattern and the etching solution composition allows the extraction of a physical model that, for the first time, clearly reveals the roles of the two fundamental kinetic mechanisms in MacEtch, carrier generation and mass transport. Ordered submicron diameter silicon via arrays with record aspect ratio are produced, which can directly impact the through‐silicon‐via technology, high density storage, photonic crystal membrane, and other related applications. Abstract : Ordered, vertical, and high aspect ratio submicron silicon via array is fabricated by metal‐assisted chemical etching. The physical model extracted from systematic variation of catalyst pattern and etching solution reveals the roles of two fundamental kinetic mechanisms, carrier generation and mass transport. This potentially disruptive etching technology can impact the formation of through‐silicon‐vias and high density electronic and photonic devices.